HAMBATAN SISWA SMK DALAM MENINGKATKAN SKILL PEMBELAJARAN APLPIG MENGGUNAKAN SOFTWARE AUTOCAD - Dahlia Dahlia (CV. ADIBA AISHA AMIRA, 2025)
The importance of education as a foundation for human growth and sustainability is highlighted, where education enables self-development and exploration of individual talents. In the context of rapid development in Indonesia, particularly in the construction sector, the importance of preparing skilled workforce through education in Vocational High Schools (SMK) is acknowledged. One key competency needed in the construction sector is proficiency in using AutoCAD software. However, learning AutoCAD in SMK faces several barriers, including students' lack of understanding and technical difficulties. Therefore, there is a need for more effective and engaging learning approaches, such as peer tutoring. Peer tutoring allows students to learn from each other and strengthen their skills and competencies. Additionally, the importance of vocational education in preparing students for entry into the industrial world, especially in the construction sector, is emphasized. The research method used is literature review, which aids in understanding and in-depth analysis of specific topics. Through this article, it is hoped that understanding of the importance of AutoCAD learning in SMK and potential solutions to enhance the quality of learning can be improved.